2023
DOI: 10.1037/bul0000404
|View full text |Cite
|
Sign up to set email alerts
|

Fenneman et al.’s (2022) review of formal impulsivity models: Implications for theory and measures of impulsivity.

Simon T. van Baal,
Jakob Hohwy,
Antonio Verdejo-García
et al.

Abstract: In Fenneman et al.’s (2022) review of theories and integrated impulsivity model, the authors distinguish between information impulsivity (i.e., acting without considering consequences) and temporal impulsivity (i.e., the tendency to pick sooner outcomes over later ones). The authors find that both types of impulsivity can be adaptive in different contexts. For example, when individuals experience scarcity of resources or when they are close to a minimum level of reserves (critical threshold). In this commentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…For example, gamble choice tasks, a staple in the decision scientists' toolbox, show weak correlations with a willingness to engage in common risky behaviors 12,13 , and are only modestly correlated with other artificial lab-based measures 14 . Similarly, paradigms designed to elicit people's time preferences show only small correlations with clinical, financial, and healthrelated intertemporal behaviors [15][16][17][18][19] . Recent analyses of field studies of behavioral interventions have likewise found small effect sizes 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, gamble choice tasks, a staple in the decision scientists' toolbox, show weak correlations with a willingness to engage in common risky behaviors 12,13 , and are only modestly correlated with other artificial lab-based measures 14 . Similarly, paradigms designed to elicit people's time preferences show only small correlations with clinical, financial, and healthrelated intertemporal behaviors [15][16][17][18][19] . Recent analyses of field studies of behavioral interventions have likewise found small effect sizes 20,21 .…”
Section: Introductionmentioning
confidence: 99%